ZCCHC3 is a co-sensor of cGAS for dsDNA recognition in innate immune response - Lian, Huan; Wei, Jin; Zang, Ru; Ye, Wen; Yang, Qing; Zhang, Xia-Nan; Chen, Yun-Da; Fu, Yu-Zhi; Hu, Ming-Ming; Lei, Cao-Qi; Luo, Wei-Wei; Li, Shu; et al. (Nature communications, 2018)
Cyclic GMP-AMP synthase (cGAS) senses double-strand (ds) DNA in the cytosol and then catalyzes synthesis of the second messenger cGAMP, which activates the adaptor MITA/STING to initiate innate antiviral response. How cGAS activity is regulated remains enigmatic. Here, we identify ZCCHC3, a CCHC-type zinc-finger protein, as a positive regulator of cytosolic dsDNA- and DNA virus-triggered signaling. We show that ZCCHC3-deficiency inhibits dsDNA- and DNA virus-triggered induction of downstream effector genes, and that ZCCHC3-deficient mice are more susceptible to lethal herpes simplex virus type 1 or vaccinia virus infection. ZCCHC3 directly binds to dsDNA, enhances the binding of cGAS to dsDNA, and is important for cGAS activation following viral infection. Our results suggest that ZCCHC3 is a co-sensor for recognition of dsDNA by cGAS, which is important for efficient innate immune response to cytosolic dsDNA and DNA virus. cGAS is an important mediator of antiviral immune responses, but the regulation of its activity is unknown. Here, the authors identify a zinc finger protein, ZCCHC3, that enhances the binding of cGAS to dsDNA and is important for its activation following viral infection.